Infection characteristics of porcine circovirus type 2 in different herds from intensive farms in China, 2022 - Fan, Mingyu; Bian, Lujie; Tian, Xiaogang; Hu, Zhiqiang; Wu, Weisheng; Sun, Leilei; Yuan, Guiqiang; Li, Shuangxi; Yue, Lei; Wang, Ying; Wu, Lili; Wang, Yongquan; et al. (Frontiers in Veterinary Science, 2023)
Porcine Circovirus type 2 (PCV2), the primary agent of porcine circovirus diseases (PCVD), has been widespread in most pig herds in the world, causing huge economic losses to the pig industry. It is crucial to study rules of the prevalence of PCV2 in different swine herds to develop effective strategies against PCVD. In this study, a total of 12,714 samples were collected from different farms in China and tested for PCV2 by qPCR to detect the positive rate and viral loads in samples from different stock classes and materials. Firstly, the results showed that PCV2 was prevalent in seventeen provinces in China, and the high-incidence areas were mainly concentrated in southern and northeastern China. Secondly, growing-finishing had the highest positive rate of total samples at 45.2%, followed by gilt sows with 42.5%. And among growing-finishing pigs, 27.2% had viral loads exceeding 106 copies/ml, whereas in sows and young pigs, just 1.9%, 3.3% had such loads. Finally, according to the data of positive detection rates and viral loads, PCV2 prevalence was showing an upward trend from piglets to adults. Using this study as a basis, it was indicated that PCV2 circulated at a very high level in pig herds in China and that it was urgent to work towards cutting off the circulation of PCV2 in pigs.